PENENTUAN DOSIS INFEKSI-50 Escherichia coli STRAIN APEC DAN GAMBARAN HISTOPATOLOGIK JANTUNG DAN HEPAR PADA AYAM BROILER UMUR 21 HARI - , DESIANA ADE MAHARI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Pathogenecity of Escherichia coli could be known by the determination of infective dose-50 in in vivo study. The objective of this study is to determinate ID50 of Avian Pathogenic Escherichia coli (APEC) in chicken and is to find out the histopathological image of chickenâs heart and liver after infected with that dose. In this study were used 42 of day old chicken (DOC) regardless their sex types. Those chickens were kept until 14 days old then were infected with APEC. The infective dose-50 was determined by Reed and Muench method. Isolation and identification of E.coli from heart and liver was cultured on eosin methylene blue (EMB) and mac Conkey agar (MCA). Biochemical reaction was tested with triple sugar iron agar (TSIA), Indole-Methyl red-Voges Proskauer-Citrate (IMVIC) test and Urea agar. Histopathological image of heart and liver was observed. The results of this study is infective dose of APEC in broiler chicken was 2 x 104,4 cell per ml (cell/ml). This dose caused damage in 35-day-aged broiler with clinical change of depression, anorexic, closing of the nictitans membrane, profuse diarrhea, dull, and general weaknesses. Microscopically of liver showed there was multifocal of heterophile infiltration around the blood vessel, and there was proliferation of Glissoni capsula with infiltration of inflammation cell and fibrin. Microscopically of heart showed there was lymphocytes and heterophile infiltration in pericardium, and thickening of pericardium.